Evaluation of Mackerel scad Fishery Management in Ternate Island Waters Based on EAFM in the Domain of Resources and Fishing Techniques - Arianto, Muhammad; Tangke, Umar; Titaheluw, Syahnul Sardi; Masiyah, Siti (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
This research was carried out in March 2021, in Sasa Village, Ternate City, South Ternate District. North Maluku Province. Data Analysis To be able to answer the purpose of this study, an analysis of the data obtained was carried out and then interpreted the data. Data analysis was carried out in stages starting from the analysis of the fish resource domain, namely the CPUE study, fish size, proportion of scad caught, species composition,